Recipes for adult stem cell plasticity: fusion cuisine or readymade?. Issue 2 (27th January 2004) - Alison, M R; Poulsom, R; Otto, W R; Vig, P; Brittan, M; Direkze, N C; Lovell, M; Fang, T C; Preston, S L; Wright, N A
Abstract : A large body of evidence supports the idea that certain adult stem cells, particularly those of bone marrow origin, can engraft at alternative locations, particularly when the recipient organ is damaged. Under strong and positive selection pressure these cells will clonally expand/differentiate, making an important contribution to tissue replacement. Similarly, bone marrow derived cells can be amplified in vitro and differentiated into many types of tissue. Despite seemingly irrefutable evidence for stem cell plasticity, a veritable chorus of detractors has emerged, some doubting its very existence, motivated perhaps by more than a little self interest. The issues that have led to this situation include the inability to reproduce certain quite startling observations, and extrapolation from the behaviour of embryonic stem cells to suggest that adult bone marrow cells simply fuse with other cells and adopt their phenotype. Although these issues need resolving and, accepting that cell fusion does appear to allow reprogramming of haemopoietic cells in special circumstances, criticising this whole new field because some areas remain unclear is not good science.